Climate Variability, Predictability and Climate Risks
DOI: 10.1007/978-1-4020-5714-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Climate risks and their impact on agriculture and forests in Switzerland

Abstract: There is growing evidence that, as a result of global climate change, some of the most severe weather events could become more frequent in Europe over the next 50 to 100 years. The paper aims to (i) describe observed trends and scenarios for summer heat waves, windstorms and heavy precipitation, based on results from simulations with global circulation models, regional climate models, and other downscaling procedures, and (ii) discuss potential impacts on agricultural systems and forests in Switzerland. Trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 101 publications
(75 reference statements)
0
50
0
Order By: Relevance
“…In addition, climate change is expected to lead to increased risk of damage from fungi, insects, spring frost, and wind (Statens Offentliga Utredningar (SOU) 2007). However, implementing pro-active risk management strategies may reduce the risk of damage in the future (Fuhrer et al 2006;Bouriaud et al 2015;Beguin et al 2016). …”
Section: Study Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, climate change is expected to lead to increased risk of damage from fungi, insects, spring frost, and wind (Statens Offentliga Utredningar (SOU) 2007). However, implementing pro-active risk management strategies may reduce the risk of damage in the future (Fuhrer et al 2006;Bouriaud et al 2015;Beguin et al 2016). …”
Section: Study Contextmentioning
confidence: 99%
“…To make forests more resistant to threats associated with climate change (e.g. increased risk of damage from wind and insects), silvicultural measures, such as more mixed forests and varying rotation length, may be implemented (Fuhrer et al 2006;Bouriaud et al 2015). Strategies used to reduce the risk of damage by animal browsing include treatments, plantation fencing, and hunting (Beguin et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, forests can easily become carbon sources rather than carbon sinks (Kurz and Apps, 1999, Gracia et al, 2001, Reichstein et al, 2002. Changes in the regimes of natural disturbances such as fire, pests or drought (Fuhrer et al, 2006, Sohngen et al, 2005, Ciais et al, 2005, can affect major forest functions, forestry outputs and forest stability. Metsaranta et al (2010) reported that Canadian forests will likely be carbon sources until 2030, and become carbon sinks after 2050, based on simulations of the impact of future fire and insect disturbances.…”
Section: Strategies To Improve Carbon Sequestrationmentioning
confidence: 99%
“…While a significant negative trend for total annual precipitation over the last two centuries in the southern part of the Alps has been shown, the average trend was positive for the northern alpine region, particularly in winter and spring (Brunetti et al 2006). An increase in amount and duration of torrential rain events, especially in winter and autumn months, during the last three to five decades has been demonstrated mainly for the northern alpine region while there is a slight positive, nonsignificant trend for the southern parts (Schmidli and Frei 2005;Fuhrer et al 2006;Diodato and Mariani 2007). In the south, these extreme events alternate with increasing dry periods in autumn and spring (Schmidli and Frei 2005).…”
Section: Effects Of Changes In Precipitation Patternsmentioning
confidence: 99%
“…However, particularly due to insufficient data availability, the linkage to riverbed clogging (reduction in riverbed interstitial flow from sediment deposition) and direct or indirect impairment on fish health by suspended sediments could not be evaluated (Fischnetz 2004). One potential cause of increased erosion and sediment loads in rivers could be increased temperatures, altered precipitation patterns (strength, timing and altitude), changes in snow cover and seasonal snow melting caused by climate change (IPCC 2007;Fuhrer et al 2006;Beniston 2006). These may have led to increased river runoff, especially in winter and in spring, and altered seasonal and regional sediment load and riverbed clogging patterns.…”
mentioning
confidence: 99%